Analysis of River Water Pollution on the Population of Tin Head Fish (Aplocheilus panchax) in an Islamic Perspective - Istiqomah, Nur; Hidayatullah, Ahmad Fauzan; Hariz, Anif Rizqianti (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
The community's disposal of various types of waste leads to a high level of water pollution, which in turn causes a decline in both water quality and quantity. Pollution is the entry or containment of living things through human activities, resulting in a decrease in quality to a certain level, which leads to the environment not operating as specified. Various types of waste contribute to pollution, creating chemical and organic compounds that pose a threat to living organisms. This study aims to record and provide information on the effect of river water pollution on the population of tinhead fish (Aplocheilus panchax) in the river Jl. Purworejo, Central Java. The research methodology was carried out on the river Jl. Purworejo, Central Java, with the tools and materials used in the form of GPS smartphones, cameras, stationery (field books, pens), fish, and garbage in the research location. We conducted descriptive exploratory research, literature reviews, and library studies. We once collected data from a garbage-covered river. Observations confirmed that there were as many as seven species of tinhead fish in river waters. The findings indicate that the presence of organic and inorganic waste in polluted waters has an impact on the quantity of tinhead fish inhabiting clean waters with lush vegetation. This report is the first piece of information regarding the influence of river water quality on Jl. Purworejo, Central Java. Other parts of the river require research and cleanup efforts.